Numerical design of microporous carbon binder domains phase in composite cathodes for lithium-ion batteries - Ge, R; Boyce, AM; Sun, Y; Shearing, PR; Grant, PS; Cumming, DJ; Smith, RM (American Chemical Society, 2023)
Lithium-ion battery (LIB) performance can be significantly affected by the nature of the complex electrode microstructure. The carbon binder domain (CBD) present in almost all LIB electrodes is used to enhance mechanical stability and facilitate electronic conduction, and understanding the CBD phase microstructure and how it affects the complex coupled transport processes is crucial to LIB performance optimization. In this work, the influence of microporosity in the CBD phase has been studied in detail for the first time, enabling insight into the relationships between the CBD microstructure and the battery performance. To investigate the effect of the CBD pore size distributions, a random field method is used to generate in silico a multiple-phase electrode structure, including bimodal pore size distributions seen in practice and microporous CBD with a tunable pore size and variable transport properties. The distribution of macropores and the microporous CBD phase substantially affected simulated battery performance, where battery specific capacity improved as the microporosity of the CBD phase increased.